Influence of miscible and immiscible sequences of poly(D-lactide) copolymers on the competition of stereocomplex- and homo-crystallization in poly(L-lactide) blends. (18th March 2021) - Li, Wenze; Wang, Mengyao; Luo, Huan; Niu, Yanhua; Huang, Yajiang; Li, Guangxian
Abstract: A high molecular weight (H M w ) PLLA has been blended with a low molecular weight (L M w ) PDLA and its two types diblock copolymers (PEG- b -PDLA and PDMS- b -PDLA), respectively, to investigate the stereocomplex (sc) and homochiral (hc) crystallization behaviors. The miscible PEG and immiscible PDMS segments with comparable molecular weight were introduced into PDLA by bulk ring-opening polymerization method. Compared to PLLA/PDLA, the introduction of both sequences could inhibit the crystallization kinetics of sc and hc crystallites of the blends due to the dilution effect of L M w segments. The formation of sc crystallites is prior to its hc counterparts. The shorter induction period of hc crystallites of PLLA/PEG-b-PDLA blend indicates that the miscible PEG segments could promote the mobility of PLLA chains. Due to the involving of PEG chains, the spherulite exhibits coarsen and irregular texture and its lamellae show sparse string-like structure. The microphase separation between PLA and PDMS segments as evidenced by SAXS results in the increased sc nuclei and different growth mode of hc crystallites. The phase separated microdomains weakened the competition between sc and hc crystallites, and the former acts as a template for repeated assembly of the latter. X-ray analysis also reveal that sc crystallites possess much thicker lamellar thickness than hc crystallites in PLLA/PDLA and PLLA/PEG-b-PDLA blends. Graphical abstract: Image 1 Highlights: The competitive crystallization kinetics of SCs and HCs tuned by introducing miscible PEG and immiscible PDMS segments. POM and AFM monitored the formation of HCs with different mode of crystal growth in PLLA/PDMS-b-PDLA blend. Miscible PEG segments could promote the mobility of PLA and result in more imperfect lamellar structure. SCs possess much thicker lamellae than HCs in PLLA/PDLA and PLLA/PEG-b-PDLA blends.